EBV-requisitioning physicians' guess on fatigue state 6 months after acute EBV infection - Tarjei Tørre Asprusten; Eva Skovlund; Vegard Bruun Wyller; Maria Pedersen (BMJ Publishing Group, 2019)
We assessed referring medical practitioner's ability to predict chronic fatigue development in adolescents presenting with acute infectious mononucleosis. Compared with 'not fatigued' being predicted as 'unsurely fatigued' and 'likely fatigued' were both strongly associated with developing fatigue 6 months later (OR 2.5, 95% CI 1.16% to 5.47% and 3.2, 95% CI 1.19% to 8.61%, respectively, P=0.012). The positive and negative predictive values were 66% and 62%, respectively. Disentangling the physician's intuition may be of interest in further investigations of risk factors and prophylactic factors for fatigue development.